2022
DOI: 10.1002/mde.3736
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial intention and resilience: An experiment during the Covid‐19 lockdown

Abstract: We study what profiles of individuals were the most likely to give up their entrepreneurial project at the beginning of the Covid‐19 crisis. To do so, we run an experiment during the first lockdown in the United Kingdom. Our results show that the first months of the crisis have a sharp screening effect: 63% of prospective entrepreneurs postpone or cancel their project in May 2020. Taste for risk or competition does not characterize those who stick to their project. Instead, low opportunity costs to continue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…Previous studies have tried to shed light on the impact of COVID-19 on different aspects of entrepreneurship, including the intention to start a business (Lopes et al 2021;Botezat et al 2022). Arve et al (2022) conducted an experiment and found that the majority of prospective entrepreneurs either canceled or postponed their projects during the first months of the pandemic. Nevertheless, some studies see this crisis as a chance to implement a business idea by establishing a firm.…”
Section: The Role Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have tried to shed light on the impact of COVID-19 on different aspects of entrepreneurship, including the intention to start a business (Lopes et al 2021;Botezat et al 2022). Arve et al (2022) conducted an experiment and found that the majority of prospective entrepreneurs either canceled or postponed their projects during the first months of the pandemic. Nevertheless, some studies see this crisis as a chance to implement a business idea by establishing a firm.…”
Section: The Role Of Covid-19mentioning
confidence: 99%
“…This reasoning leads to the concept of resilience, which refers to the ability that a person has to recover from or adjust easily to change or misfortune (Sinclair and Wallston 2004;Alshebami and Seraj 2022a). Studies have shown that resilience is an important factor in crisis settings, including in entrepreneurship (Arve et al 2022;Bullough et al 2014;Sharma and Rautela 2021;Schepers et al 2021;Alshebami 2022). Prior research has found that perceived behavioral control is affected by crises, including COVID-19, supporting the existence of this association (Prasetyo et al 2020;Srisathan and Naruetharadhol 2022).…”
Section: The Role Of Covid-19mentioning
confidence: 99%
“…The extant literature has almost exclusively considered the effects of lockdown severity (Arve et al, 2022; Ashraf, 2020; Chakrabarty & Mukherjee, 2022; Goolsbee & Syverson, 2021; Gottlieb et al, 2020; Koren & Peto, 2020; Nagarajan & Sharma, 2021; Ratto et al, 2021, and Galiani, 2022 for a more general perspective). In contrast, this paper's novel focus on the determinants of lockdown severity should be informative in guiding policy in future pandemics and for nations that were relative laggards in policy responses to the current pandemic (also, see related, Ferraresi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…3 Third, island nations figure in both the most aggressive and least aggressive lists. Finally, Scandinavian nations (Sweden, Iceland, Finland, and Denmark) The extant literature has almost exclusively considered the effects of lockdown severity (Arve et al, 2022;Ashraf, 2020;Chakrabarty & Mukherjee, 2022;Goolsbee & Syverson, 2021;Gottlieb et al, 2020;Koren & Peto, 2020;Nagarajan & Sharma, 2021;Ratto et al, 2021, andGaliani, 2022 for a more general perspective).…”
mentioning
confidence: 99%
“…The outbreak of the COVID-19 pandemic has had a detrimental impact on developing countries, especially nations with partial state incentives and financial assistance (Aqeel et al, 2022; Arve, Desrieux & Espinosa, 2022; Ge et al, 2022). Many countries implemented lockdown measures and imposed restrictions on movement to reduce the spread of the virus, adversely affecting entrepreneurial activities across various sectors (Aqeel et al, 2022; Kuckertz et al, 2020; Nasar et al, 2022; Tang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%